Adolphus Washington Greely (1844-1935) - Todd, Alden (ARCTIC, 1985)
Adolphus Washington Greely became a world celebrity almost overnight in 1884 when the six survivors of the Lady Franklin Bay Expedition under his leadership were rescued from starvation in the Arctic. Yet he was far more than the central figure of one tragic expedition. Explorer, soldier, scientist, and author, Greely was respected as an international authority on polar science from the 1880s until his death 50 years later. . By the time he retired as a major general in 1908, he had set a record as the first soldier to enter the U.S. Army as a private and achieve a general's rank. . Greely's particular interest early on lay in telegraphic signaling, which had proved itself during the war, and the use of meteorological reports sent by telegraph to predict changes in weather. By 1869 he was detailed to Washington as a signal officer. Here he fell under the spell of Captain Henry W. Howgate, a Signal Service officer who was an enthusiast for arctic exploration and who opened his extensive library of arctic literature to the younger officer. It was through this chain of events that Greely was inspired to a deep interest in leading an arctic expedition. . The plan was for Greely's party to spend two years at Lady Franklin Bay - from summer 1881 to summer 1883 - exploring the coasts, documenting the wildlife, and carrying out other observations going beyond the program of the Hamburg Conference. A supply ship was scheduled to bring mail and relief personnel in summer 1882 and to return in 1883 to bring the party home with its scientific finds. By August the expedition of 25 men was comfortably installed in a large wooden building assembled from lumber brought on shipboard. A plentiful supply of fresh musk-ox meat was on hand, thanks to the expedition hunters, and there was adequate coal hacked from an outcropping a few miles to the east that had been found by the Nares Expedition in 1875. During the following 24 months, the expedition carried out the prepared program of scientific observations and measurements in ...